Teachers’ Perceptions about Dyslexia and Intervention with Students at Risk of Dyslexia in the United Arab Emirates (UAE) Schools - BENKOHILA, NORA (2018)
Research proved that raising the phonological and phonemic awareness among students may help students at risk not to be future dyslexic.Moreover, teachers awareness play a vital role in identifying students with dyslexia and help them to apply the suitable intervention for students with dyslexia. Therefore, the objective of this study was two-fold as follows: to investigate: a) teachers in UAE awareness about dyslexia and the appropriate use of intervening measures to serve students with dyslexia, and b) the teachers awareness influence on intervention quality with students with dyslexia A convergent parallel mixed methods design was adopted to collect data, 29 teachers participated in answering the questionnaire designed for quantitative data collection, and at the same time a case study was conducted to qualitatively provide insights into the context from an intervention with a dyslexic student. Findings indicated that while teachers expressed fair understanding of dyslexia as a reading disability, they expressed confusion about traits of dyslexia. Also, teacher’s awareness about dyslexia may positively impact identifying and serving students with dyslexia. Furthermore, raising the phonological and phonemic awareness of the student with dyslexia in the case study showed amazing results.